GENDER DIFFERENCES IN SOCIAL NETWORKING SITES USAGE AMONG STUDENTS: EVIDENCE FROM KOFORIDUA TECHNICAL UNIVERSITY, GHANA. - Ameyaw Samuel,; Asante Antwi Edward,; Asante Edward, (IJRDO - Journal of Social Science and Humanities Research, 2017)
The study sought to find out gender differences in the usage of social networking sites (SNSs) among students with a focus on Koforidua Technical University (KTU) Campus.The questionnaire was used for data gathering. A total of 258 copies of questionnaire were distributed, 246 were retrieved representing 95.3% response rate, which was very much representative of the sample. The statistical package for social sciences (SPSS 16.0 version) was used in data analysis. The study revealed that majority of the respondents visit SNS daily and spend 1-2 hours a day. Also, the study disclosed that the use of SNSs had negatively affected their academic performance. The study recommends, among others that students should be encouraged to use SNSs for academic purposes rather than non-academic activities and also to reduce the number of hours spent on SNSs per day. They should be encouraged to visit the library regularly to improve their reading habits and academic performances as well.